Radical Solutions and eLearning Practical Innovations and Online Educational Technology - Burgos, Daniel ca. 20./21. Jahrhundert (Lecture Notes in Educational Technology, 2020)
Educational Technology is the right couple to a radical innovation. Thanks to the appropriate technology in the right context with the best fit to the target audience, education can be drastically improved, meaning a better performance, competence achievement, match with the user’s expectations and with the market needs. Serious games, Virtual reality, Augmented reality, Remote labs, Online learning, Blockchain, Mobile learning and many other key technologies allow for a better explanation of so many subjects, and even more: for a complete student involvement and a full teacher engagement into the educational system. Technology gives another angle to the same content, provides the user with a personalised experience and pushes the limits of knowledge a little further, every time. This book presents a number of radical innovations through technology, from experienced cases studies, to be replicated and inspired by; a powerful resource handbook for cutting-edge education